On the Impact of the Caribbean Counter Current in the Guajira Upwelling System - Orfila, Alejandro; Urbano-Latorre, Claudia P.; Sayol, Juan M.; Gonzalez-Montes, Stephanie; Caceres-Euse, Alejandro; Hernández-Carrasco, Ismael; Muñoz, Ángel G. (Frontiers in Marine Science, 2021)
The variability of La Guajira upwelling system, in the south-central Caribbean Sea, is strongly influenced by the intensity and location of the atmospheric Caribbean Low-Level Jet (CLLJ), a near-surface branch of the easterlies, as well as by the regional ocean circulation. During favorable conditions (i.e. strong easterlies blowing almost parallel to the coast), upwelling is enhanced and a large amount of primary productivity occurs in La Guajira area. In contrast, during relatively mild wind conditions, the CLLJ is misaligned to the coast and the Caribbean Counter Current (CCC, locally also known as the Darien Current), which forms as a branch from the Panama-Colombia Gyre, flows northeastward over the continental shelf advecting waters from the southwestern Caribbean basin towards La Guajira. The CCC has a clear signature at the surface layer that extends from the Darien Gulf towards La Guajira peninsula during mild wind periods, while disappears during the months of strong winds. The direction and the magnitude of the easterlies, and more specifically of the CLLJ, control the position and pathway of the CCC, which extends more than 900 km in the southern Caribbean Sea during May, June, August, September and October. The high concentration of chlorophyll-a at the sea surface evidenced by satellite-based colour images is semi-seasonally modulated by the CLLJ, which during its relaxation phase allows the irruption of the CCC towards the east up to La Guajira.